Применение беспилотных летательных аппаратов в боевой информационно-управляющей системе бронетанковой техники - Анипко, О. Б.; Сиренко, С. Н.; Ковтонюк, И. Б. (НТУ "ХПИ", 2015)
Розглянуто застосування безпілотних літальних апаратів для пошуку та виявлення цілей, що дасть можливість підвищити ефективність комплексу управління вогнем бронетанкової техніки.

Use of unmanned aerial vehicles for search and detection of targets has been studied, which shall enable to enhance efficiency of armored equipment fire control system.
Application of unmanned aerial vehicles in battle management system of armored equipment
Keywords: бротехника; бронетанковая техника; беспилотные летательные аппараты; комплекс управления огнем